Determinants of government bond spreads in the Euro Area - in good times as in bad - Jens Boysen-Hogrefe; Christian Aßmann (Verein für Socialpolitik, 2010)
Despite the single currency, yields on government bonds in the Euro Area deviate substantially from German bond yields. These bond spreads are usually attributed to differing default and liquidity risks. The empirical literature documents that evaluation of these risks is subject to time variation in global factors approximated by US corporate bond spreads or short term interest rates. Within this paper time variation is modeled via latent processes instead of proxy variables. The findings suggest that default risk measured via expected debt to gross national product ratio explains a major part of the differences in band yields in the Euro area between 2003 and the unfolding of the financial crises. During the financial crises both risks gain importance in explaining bond spreads, with increased relative importance of liquidity risks compared to default risks or their market perception.
Keywords: E62; C23; G12; 330; Euro Area; bond spreads; time-varying coefficients; liquidity risk; default risk